The Impact of Covid-19 Social Isolation on Mental Health and Physical Activity of Older Adults - Kistiana, Sari (Universitas Airlangga, 2023)
Background: The ongoing COVID-19 pandemic tends to affect older adults more severely, raising the need for social isolation in this age population. Social isolation is likely to impact older adults' social ties and quality of life, as well as the risk for illness and health. Objective: This study is a narrative literature review to evaluate the potential effects of social isolation on the mental health and well-being of older adults. Methods: A literature search performed between January 1, 2020, and January 13, 2021, comprised an electronic search on different online databases in PubMed and ScienceDirect using the keywords COVID-19 followed by generic terms older adults or older people or aging population or elderly. Excluding duplicates, a total of 376 articles were screened, of which 21 studies were included in the final review. Results: Many older people could be mentally well-equipped to deal with social isolation, but some experience a negative impact on mental health. Stress, anxiety, and depression symptoms were reported during the self-isolation period. Physical activity also has declined among older adults amid COVID-19. Some elderly who are not moving much may lose significant muscle strength, flexibility, and aerobic capacity. Conclusion: If social isolation continues, policy responses such as proactively identifying and addressing COVID-19 for the elderly who are experiencing negative consequences. An effective solution such as